2018
DOI: 10.20473/bhsj.v1i2.9400
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patients with End-Stage Renal Disease at Dialysis Unit Dr. Soetomo General Hospital Surabaya

Abstract: Introduction: The prevalence of end stage renal disease (ESRD) in Indonesia is increasing over the last decade. Most cases highest risk factor are Diabetes Mellitus (DM) and hypertension. Other factors such as lifestyle and environment; both play important role in the development of ESRD. Thus, this study aimed to assess the characteristic of patient with ESRD.Methods: This was a descriptive study acquired by interviewing 126 patients with ESRD who have been undergoing continuous hemodialysis in dialysis unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
0
11
0
3
Order By: Relevance
“…Hypertension was the primary cause of stage 5 CKD in Indonesia in 2018, with a presentation of 36%, and diabetes was the second most prevalent cause (28%) (Indonesian Renal Registry Team, 2017). In a study conducted by Farida, Thaha, & Susanti (2018) in the dialysis unit of the Dr. Soetomo Hospital with patients with stage 5 CKD, as many as 28.60% of respondents had smoking habits. Meanwhile, Anthoni, Supriyadi, & Fatimah (2019) found that 53% of their respondents with CKD also suffered from obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension was the primary cause of stage 5 CKD in Indonesia in 2018, with a presentation of 36%, and diabetes was the second most prevalent cause (28%) (Indonesian Renal Registry Team, 2017). In a study conducted by Farida, Thaha, & Susanti (2018) in the dialysis unit of the Dr. Soetomo Hospital with patients with stage 5 CKD, as many as 28.60% of respondents had smoking habits. Meanwhile, Anthoni, Supriyadi, & Fatimah (2019) found that 53% of their respondents with CKD also suffered from obesity.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, our study is the first in Indonesia to study CKD and CKDu prevalence in a general working population, i.e., among farmers that are still actively working. Most of the CKD studies in Indonesia have focused on subjects already diagnosed with kidney disease [ 16 , 17 , 18 , 19 , 20 ]. We used common diagnostic criteria for CKD, similar to other studies of working populations in El Salvador [ 3 ] and Malaysia [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, no study has been conducted to investigate the prevalence of CKDu and its risk factors in the agricultural population in Indonesia. We found some studies on CKD in Indonesia, but not CKDu and these studies focused only on subjects already diagnosed with kidney disease [ 16 , 17 , 18 , 19 , 20 ]. As unknown causes in CKD are more common in countries of Asia [ 2 ], we interested to conduct a study obtaining a prevalence estimate of CKDu in farmers in Indonesia and its risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, it is estimated that as many as 5-10 million people die each year due to kidney failure (Luyckx et al, 2017). Data from the dialysis unit of Dr Soetomo Hospital Surabaya shows an increase in patients who routinely undergo routine hemodialysis twice a week in the last three years; 245 patients in 2013, 255 patients in 2014 and 303 patients in 2016 (Farida et al, 2018).…”
Section: Introductionmentioning
confidence: 99%